2019
DOI: 10.3892/etm.2019.7837
|View full text |Cite
|
Sign up to set email alerts
|

An inventory of medicinal products causing skin rash: Clinical and regulatory lessons

Abstract: A variety of medicinal products have been associated with rash and normally this information should be available in the Summary of Product Characteristics (SmPCs). Our study aimed to investigate the frequency of rash as an adverse drug reaction, based on the information provided by SmPCs of 1,048 single active substances (international non-proprietary names) authorized in the United Kingdom. Data on rash frequency was collected from each SmPC using automated searches based on selected keywords. Data analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…A study indicated that the rash was a very rare adverse reaction associated with torasemide. Only around 3 % of the 1,048 medicines analyzed developed rashes (Ancuceanu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that the rash was a very rare adverse reaction associated with torasemide. Only around 3 % of the 1,048 medicines analyzed developed rashes (Ancuceanu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A further consideration to this route of administration is the requirement of significantly higher doses to achieve the proposed 15-30 mg/L therapeutic levels. If it is feasible to develop transdermal patches to achieve such levels, the risk of local skin reactions, which is a known side-effect of transdermal melatonin may become a concern [145]. There are some limitations of current animal models for NE in the LMIC setting.…”
Section: Melatonin As a Single Agent For The Low Resource Settingmentioning
confidence: 99%
“…Some other rare reactions to antibiotics are rashes, but patients with low urinary tract symptoms, especially the stocking symptoms, often receive overactive bladder syndrome diagnosis and treatment. Anticholinergic treatment can also cause rashes in up to 3.06% [16] and by the time the patients receive antibiotic treatment for the correct diagnosis adverse effects of antibiotics might overlap with the previous medication. For this reason, we decided not to follow rare adverse effects in our study.…”
Section: Escherichia Coli Resistancementioning
confidence: 99%